Bee-ing similar: low diversity, no population structure, and signals of adaptation in two North Dakota bumble bees - Rhiannon Hall; Meggan A. Alston; Jason P. Harmon; Clint R. V. Otto; Travis Seaborn (Biodiversity and Conservation, 2026)
Habitat fragmentation and destruction are driving widespread declines in ecosystem function, species abundance, and genetic diversity across the globe. Among the affected taxa are bumble bees (genus Bombus ), which are essential pollinators. Bumble bee declines have been linked to anthropogenic pressures such as land-use change and climate change. To better understand how the environment is shaping bumble bee populations, we employed a landscape genetics approach to examine the genetic diversity, population structure, and potential local adaptation of two widespread species— Bombus ternarius and Bombus griseocollis —across North Dakota. From 2017–2020, 161 B. ternarius and 200 B. griseocollis bumble bees were sampled in ND across 13 and 17 sites, respectively. We found low levels of heterozygosity and inbreeding across all populations for both species, with no evidence of population structure or isolation by distance. Our results revealed signatures of potential local adaptation to climatic variables and land cover characteristics, suggesting that our species are adapted to environmental gradients across the state. Having similar results between both species across all analyses suggests that other wide-ranging bumble bees in the region may share these patterns. High connectivity can buffer short-term population losses, but low genetic diversity may constrain adaptive potential and reduce resilience to future environmental change and emerging threats. Our findings have broad applicability to other pollinators and taxa facing similar environmental pressures. Both species have populations that continually exchange genes creating widespread connectivity but are still locally shaped by adaptation.